2021
DOI: 10.3390/su14010445
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Assisted Phytostabilization for Potentially Toxic Element Immobilization

Abstract: In response to the growing threat to the quality of the soil environment, new technologies are being developed to protect and remediate contaminated sites. A new approach, namely, assisted phytostabilization, has been used in areas contaminated with high levels of potentially toxic elements (PTEs), using various soil additives. This paper determined the effectiveness of biochar-assisted phytostabilization using Dactylis glomerata L. of soil contaminated with high concentrations of the selected PTEs (in mg/kg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…In support of the current study, several investigations have demonstrated that the addition of lime and biochar keeps mineral nitrogen in the soil longer by preventing it from leaching [29,31,32]. By contradicting this present study's fndings, Radziemska et al [41] observed higher rates of nitrifcation on severely acidic soil when liming is administered. Te highest soil TMN concentration of Farm-1's control treatment may be because of the soil's relatively inherent N content and higher rate of nitrogen mineralization in soils with low C/N rates.…”
Section: Soil Ammonium (Nh 4 -N) and Nitrate (No 3 -N) Andsupporting
confidence: 47%
See 2 more Smart Citations
“…In support of the current study, several investigations have demonstrated that the addition of lime and biochar keeps mineral nitrogen in the soil longer by preventing it from leaching [29,31,32]. By contradicting this present study's fndings, Radziemska et al [41] observed higher rates of nitrifcation on severely acidic soil when liming is administered. Te highest soil TMN concentration of Farm-1's control treatment may be because of the soil's relatively inherent N content and higher rate of nitrogen mineralization in soils with low C/N rates.…”
Section: Soil Ammonium (Nh 4 -N) and Nitrate (No 3 -N) Andsupporting
confidence: 47%
“…However, the Farm-2 soil had recorded the opposite process. It is probable that in this situation, denitrifcation is taking place more slowly than nitrifcation [41,96].…”
Section: Relationships Between the Physical And Chemical Parameters O...mentioning
confidence: 99%
See 1 more Smart Citation
“…compost, biochar, zeolites, water treatment residuals, red muds, and lime) (Barbosa and Fernando, 2018;Castaldi et al 2018;Fiorentino et al, 2018;Garau et al, 2022). This kind of approach, which is defined as assisted phytoremediation, was successfully applied in many instances for the remediation of PTE-contaminated soils (e.g., Liu et al 2022;Radziemska et al 2022;Zeremski et al 2021), but very limited and inconsistent information is available for sorghum.…”
Section: Introductionmentioning
confidence: 99%